Perspective of the Educational Community about the Performance of School Directors: Some Reflections - Ileana Vargas-Jiménez (Universidad Nacional, Costa Rica, 2016)
Two educational institutions were selected with the aim of characterizing the performance of two principals from the perspective of the educational community: teachers, students, administrative assistant and parents. In order to carry out the study, it was necessary to consider how the members of the educational community of two schools evaluate the professional performance related to the exercise of leadership, communication processes and decision making, during the internship of two CIDE graduates of the UNA. We worked the interviews and the focus groups with twenty-eight participants; later, we used the ATLAS TI tool to interpret the analysis categories. The main conclusions are that a quality management must be a process of participation, teamwork, communication and approach from the school administration to the people involved. Likewise, it is conceived that a good performance means to consider students as a priority, to help others with humility and affection, to know how to listen, to provide confidence; and that the principal considers students as a priority, and is a negotiating person who knows how to delegate. In short, a good principal is the person who can lead an institution by exercising good leadership, and, therefore, will influence the proper management of communication and decision-making.